Offsetting Expression Profiles of Prognostic Markers in Prostate Tumor vs. Its Microenvironment - Jia, Zhenyu; Zhu, Jianguo; Zhuo, Yangjia; Li, Ruidong; Qu, Han; Wang, Shibo; Wang, Meiyue; Lu, Jianming; Chater, John M.; Ma, Renyuan; Liu, Ze-zhen; Cai, Zhiduan; et al. (Frontiers in Oncology, 2019)
Diagnosis of the presence of tumors and subsequent prognosis based on tumor microenvironment becomes more clinically practical because tumor-adjacent tissues are easy to collect and they are more genetically homogeneous. The purpose of this study was to identify new prognostic markers in prostate stroma that is near to tumor. We have demonstrated the prognostic feature for FGFR1, FRS2, S6K1, LDHB, MYPT1 and P-LDHA in prostate tumor using tissue microarrays (TMAs) which consist of 241 patient samples from Massachusetts General Hospital (MGH). In this study, we investigated these six markers in tumor microenvironment using an Aperio Imagescope system in the same TMAs. The joint prognostic power of markers was further evaluated and classified using a new algorithm named Weighted Dichotomizing. The classifier was verified via rigorous 10-fold cross validation. Statistical analysis of the protein expression indicated that in tumor-adjacent stroma FGFR1 and MYPT1 were significantly correlated with patient outcomes and LDHB showed the outcome-association tendency. More interestingly, these correlations were completely opposite in tumor tissue as previously reported. The results suggest that prognostic test should utilize either tumor-enriched tissue or stroma with distinct signature profiles, rather than using mixture of both tissue types. The new classifier based on stroma tissue has potential value in clinical management of prostate cancer patients.